LINKING COLLEGE TEACHERS’ LEARNING AGILITY WITH THEIR JOB PERFORMANCE (Contemporary Journal of Social Science Review, 2025)
The present study was designed to find out relationship between learning agility and job performance of teachers at college level, This study was quantitative in  nature and correlation research design was used for this research ..The population consisted of teachers serving at public colleges in Lahore. Multistage sampling technique was used. The sample was consisted of twelve public colleges. Data were collected from a sample of 400 college teachers through adopted questionnaire that was developed by Gravett and Caldwell (2016) for learning agility and. job performance scale developed by Koopmans et al. (2014). learning agility had four factors people agility, mental agility, result agility, and change agility while job performance had three factors task performance,contextual performance and counterproductive work behaviore.  The cronbach alpha coefficient of relability for learning agility scale was 0.83 while for job performance scale was 0.87. Correlation analysis showed that significant moderate positive relationship exists between learning agility and job performance of college teachers. It is suggested Colleges should support instructors in developing their learning agility skills as employment performance is favourably correlated with learning agility.